MY ADVICE RESEARCH ADVISOR TEACHING FOREIGN LANGUAGE IN EASY WAY - Diyoraxon Alijonova Murodjonovna; Akhmedova Matlubahon Ibragimdjonovna (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation: This article explores innovative and effective methods for teaching foreign languages with an emphasis on simplicity and ease of learning. Drawing on current pedagogical research and technology integration, the article provides insights into practical strategies that instructors can employ to enhance student engagement and language acquisition. The study employs a mixed-methods approach, combining literature analysis and empirical research to evaluate the efficacy of these teaching methods.